Gestión de inventarios y disponibilidad de materiales en el Hospital Santa Gema de Yurimaguas 2022 - Montero Peñaherrera, Marvin Steven (2023)
The research was developed with the objective of specifying the degree of relationship between inventory management and availability of materials at the Santa Gema Yurimaguas Hospital in the year 2022. Applied research was used, with a descriptive-correlational approach and a non-experimental design. The sample for the study consisted of 85 workers. The data collected was obtained through a survey. recording the data in a questionnaire, finally managed to conclude that: the results of inventory management in the hospital, it is known that they have been given regular management, this is due to the fact that the areas of the hospital sometimes have formats for the exit and reception of contents and supplies from the warehouse. In the same way, the availability of materials in the hospital is classified as regular, because, although it is divided according to the classification of materials, the stock is not always fulfilled in less time. Even so, a faster and more adequate distribution is achieved. Finally, the correlation between the variables was determined, which was confirmed by a coefficient and a significance of (r=0.652; p=0.000).